Perancangan Tipikal Jembatan Menggunakan Metode Building Information Modeling - Agus Sutiono; Veronika Happy Puspasari (Program Studi Teknik Sipil Fakultas Teknik Universitas Palangka Raya, 2024)
The development of technology is currently a challenge in the construction field. Building Information Modeling (BIM) is an example of technological advances in the construction field that help projects to be completed effectively and efficiently. Project planning for flood control works on the Sanggai River in Bumi Harapan Village was carried out to prevent flooding. Bumi Harapan Village, located in Sepaku Sub-district, Penajam Paser Utara District, East Kalimantan, is the planned capital city of the